Rediseño e implementación de un sistema de monitoreo de temperatura y conductividad eléctrica del agua del suelo de la reserva biológica San Francisco. - Tuza Cuenca, Manuel Agustín (2019)
This thesis work is oriented to the redesign of a monitoring system for the variables of temperature and electrical conductivity of soil water, for later implementation in a meteorological station of the San Francisco Biological Reserve. It is part of subproject A2 “Simulating response mechanisms and effect of global climate change on hydrological flows in tropical montane ecosystems”, of the RESPECT project (Environmental Changes in Megabiodiversity Ecosystems in Southern Ecuador: Effects of Responses and Feedback). For the redesign, devices (sensors, tentacle shield, RTC module, SD module) compatible with the free software platform Arduino are implemented, for later assembly, and finally its implementation is carried out. A series of tests are carried out to verify the correct acquisition and storage of data, in order to validate the operation of the implemented system, to carry out the analysis and discussion of the results obtained and subsequently elaborate and present the conclusions and recommendations of the work of thesis carried out.